MEMAHAMI DAN MEMANFAATKAN PENELITIAN DALAM KARYA-KARYA KEAGAMAAN - John Tondowidjojo (Bahasa Indonesia, 2018)
Some of development in this world came from research at the begining. It means that research is one of the very important thing to make something comes true. Spesifically, this article want to give some information how to use the power of research for developing the relogious works. By the way, research at the beginning of each religious works will be make them powerfull and adequate benefit.